Prudential discipline for financial firms: Micro, macro, and market structures - Larry D. Wall (Federal Reserve Bank of Atlanta, 2010)
The recent global financial crisis reflects numerous breakdowns in the prudential discipline of financial firms. This paper discusses ways to strengthen micro- and macroprudential supervision and restore credible market discipline. The discussion notes that microprudential supervisors are typically assigned a variety of goals that sometimes have conflicting policy implications. In such a setting, the structure of the regulatory agencies and the priority given to prudential goals are critical to achieving those goals. The analysis of macroprudential supervision emphasizes that this supervisor must be both bold and modest: bold in seeking to understand the sources and distributions of systemically important risks and modest about what a supervisor can do without imposing overly restrictive regulations. Finally, the paper argues that the primary responsibility for risk management must rest with firms, not government supervisors. Unfortunately, systemic risk concerns have led governments to shield the private sector from the full losses that dull their incentive to discipline risk taking. This section of the paper suggests that deposit insurance reform, special resolutions for systemically important firms, and requirements that firms plan for their own resolution and contingent capital may all have a role to play in restoring effective market discipline.
Keywords: G28; E44; K23; 330; financial; microprudential; macroprudential; market discipline